Impact of Debye plasmas environments on He-like ions and He-atom collisions. (July 2015) - Pandey, Mukesh Kumar; Ho, Yew Kam
Synopsis: The impact of Debye plasmas on the electron capture and ionization process is investigated in multiply charged He-like ion (Li +, Be 2+, B 3+, C 4+, N 5+, O 6+ ) and He atom collisions.